SEMANTIC ANALYSIS OF MEANING IN THE MIRROR POETRY ANTHOLOGY BY HADI MULYADI - Amalia Firda Fahraniah; Putri Aulia Alpin; Fikri Hakim (Media Inovasi Pendidikan dan Publikasi, 2024)
This research analyzes the language style in the poetry anthology